Enhancing Tourism Destinations Through Promoting the Variety and Uniqueness of Attractions Offered by Minority Populations: An Exploratory Study Towards a New Research Field - Pechlaner, Harald; Beritelli, P.; Pichler, S. (Emerald, 2014)
Purpose: Minority areas, with their cultural distinctiveness and a strong tendency to cultivate and preserve cultural identities, can offer guests special added value as tourist destinations. This study seeks to address whether and to what extent locals and guests of tourist areas populated by minority populations perceive and are aware of the uniqueness, variety and potential of the minority in a region. Design/methodology/approach: Research has already been developed that analyses the inter‐relations between the local population and tourism, but is scarce regarding national minorities and tourism. This paper pursues a new research field focusing on the potential of tourist destinations that offer specialised characteristics due to their cultural, ethnic or minority populations. The authors carried out an empirical study using quantitative, standardised questionnaires in 2008 in two minority areas: South Tyrol, Italy (which has a Ladin minority population) as well as Transylvania, Romania (which has a German and Hungarian minority population). The South Tyrol situation is doubly unusual, because the Ladin minority population is a minority within the German minority region in Italy.Findings: The study shows that ethnic minority populations can definitely offer added value for holidaymakers in tourist destinations. The special interest and attraction of these types of holiday stay for guests is explained, above all, by the varied cuisine and the locals' proficiency in languages (South Tyrol) as well as the specific architecture and the more extensive cultural offerings (Transylvania). In Transylvania no significant differences and in South Tyrol significant differences in the perception of the special cultural situation by locals and guests have been observed. Research limitations/implications: This study was confined to 250 interviewees per group and study region, due to budget restrictions. Compared to the volume of research on native population and tourism, research on minorities and tourist activities is quite new. Therefore this research paper provides only an exploratory study and could be developed further. Originality/value: The paper shows that ethnic minorities, with their customs and traditions, languages and architectural styles, can definitely offer added value for holidaymakers.